2024
DOI: 10.9734/jpri/2024/v36i27499
|View full text |Cite
|
Sign up to set email alerts
|

Role of Topical and Systemic Medications in Orthodontics: A Review

Felwa Sulaiman AlHudaithi

Abstract: Prescriptions for medications have increased significantly over time. The primary reason for this growth has been the rise in demand for drugs that effectively treat age-related and chronic disorders. Additionally, other variables like health insurance companies and medical ads have had a big impact on the development. Despite the rise in the use of these drugs, researchers claim that children and teenagers are becoming more and more in need of orthodontic treatment. It is evident that individuals who use over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…This type of pain is directly proportional with the force applied by the appliance that may require pharmacological intervention (61,62) . The most commonly used drugs are the over the counter (OTC) analgesics and non-steroidal anti-inflammatory drugs (NSAIDs) (11,62,63) . Mofti et al found that paracetamol and ibuprofen are the most frequently used and effective analgesics with a parallel effect in alleviating the orthodontic pain (62) .…”
Section: Digital Prescriptions and Pharmacist Role In Supporting Orth...mentioning
confidence: 99%
“…This type of pain is directly proportional with the force applied by the appliance that may require pharmacological intervention (61,62) . The most commonly used drugs are the over the counter (OTC) analgesics and non-steroidal anti-inflammatory drugs (NSAIDs) (11,62,63) . Mofti et al found that paracetamol and ibuprofen are the most frequently used and effective analgesics with a parallel effect in alleviating the orthodontic pain (62) .…”
Section: Digital Prescriptions and Pharmacist Role In Supporting Orth...mentioning
confidence: 99%